Predictors of a negative labour and birth experience based on a national survey of Canadian women. Issue 1 (December 2016) - Smarandache, Andrei; Kim, Theresa; Bohr, Yvonne; Tamim, Hala
Abstract Background A negative birth experience has been shown to have a significant impact on the well-being and future choices of mothers. The objective of this study was to assess the prevalence of, and identify the risk factors associated with a negative birth experience for women in Canada. Methods The study was based on secondary data analysis of the Maternity Experiences Survey (MES), a Canadian population database administered to 6, 421 Canadian women in 2006. The examined outcome - negative birth experience – was derived from mothers' self-report of overall labour and birth experience. Independent variables were maternal demographics, health characteristics, pregnancy-related characteristics, and birth characteristics. Multivariable logistic regression analysis was performed to determine the significant predictors of negative birth experience. Adjusted Odds Ratios (AOR) and 95 % Confidence Intervals (CI) are reported. Results Negative birth experience was reported among 9.3 % of women. The main significant predictors of a negative birth experience included older age (AOR 2.29, 95 % CI, 1.03–5.07), violence experienced in the past two years (AOR, 1.62, 95 % CI, 1.21–2.18), poor self-perceived health (adjusted OR, 1.95, 95 % CI, 1.36–2.80), prenatal classes attended (adjusted OR, 1.36, 95 % CI, 1.06–1.76), unintended pregnancy (adjusted OR, 1.30, 95 % CI, 1.03–1.63), caesarean birth (AOR, 1.65, 95 % CI, 1.32–2.06), and neonate admission to intensive care (AOR, 1.40, 95 % CI, 1.08–1.82). Conclusion Significant predictors of a negative labour and birth experience were identified through this study, a first in the Canadian context. These findings suggest future research directions and provide a basis for the design and evaluation of maternal health policy and prevention programs.